Is AI Approved by the FDA for Medical Use? A Deep Dive into the Regulatory Landscape - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Is AI Approved by the FDA for Medical Use? A Deep Dive into the Regulatory Landscape The integration of Artificial Intelligence (AI) and Machine Learnin...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care